A new formulation for fast calculation of far field force in molecular dynamics simulations - Chau, Nguyen Hai (VNU Journal of Science: Mathematics - Physics; Vol 23 No 1, 2007)
We have developed a new formulation for fast calculation of far-field force of fast multipole method (FMM)in molecular dynamics simulations. FMM is a linear algorithm to calculate force for molecular dynamics simulations. GRAPE is aspecial-purpose computer at the same price. However FMM cannot be implemented directtly on GRAPE. We have succeeded to implement FMM on GRAPE adn developed a new formulation for far-field force calculation. Numerical tests show that the performance of FMM using our new formulation on GRAPE is approximately 2-5 times faster than that of FMM using conventional far field formulation.